Effectiveness and safety of fire needle for knee osteoarthritis: A protocol of systematic review and meta-analysis. Issue 3 (22nd January 2021) - Lu, Lunbin; Ye, Jing; Xiong, Jun; Chen, Jun; Zhu, Siyuan; Zhong, Zhiying; Tang, Genhua; Zhou, Xingchen; Guo, Han
Abstract: Background: There is a lack of curative medical treatment for patients with knee osteoarthritis (KOA). Acupuncture represents an important alternative therapy. In various forms of acupuncture and moxibustion, the fire needle is an indispensable part. Knee osteoarthritis (KOA) is a series of symptoms and signs of knee joint caused by local injury and inflammation and chronic strain of the knee joint resulting in cartilage degeneration of the articular surface and reactive bone loss of the subchondral bone plate. The results of clinical trial indicated that the fire needle therapy has obvious curative effect in treating KOA. This protocol is intended to describe how to collate and accumulate evidence for the current efficient and safe treatment of KOA with fire needle. Methods: Seven electronic databases were used to retrieve the literature for the KOA randomized controlled trials, including 3 English databases (PubMed, EMBASE, the Cochrane Central Register of Controlled Trials [Cochrane Library]), and 4 Chinese databases (Chinese National Knowledge Infrastructure, Chinese VIP Information, Wanfang Database, and Chinese Biomedical Literature Database). This systematic review will include all randomized controlled clinical trials using fire needle therapy for KOA. The observation Index is the Change of Western Ontario and McMaster Universities Osteoarthritis Index Total, first proposed by Bellamy in 1988. The selection of the study will be completed independently by 2 reviewers, extract the data, and evaluate the quality of the study before selecting the title, abstract, and full text. Revman 5.4 software will be used to perform meta-analyses of randomized controlled trials, where risk ratios for dichotomous data and standardized or weighted mean differences for continuous data are the results. Result: The results will be published in a peer-reviewed journal. Conclusion: This systematic review will provide the latest evidence to evaluate the safety and efficacy of fire needle therapy in patients with KOA. Trial registration number: INPLASY202080030